Measurement of the B0s→D(*)+sD(*)− branching fractions - Cheung, S; Evans, T; Gandini, P; Hadavizadeh, T; Harnew, N; Hill, D; Jalocha, P; John, M; Lupton, O; Malde, S; Nandi, A; Topp-Jorgenson, S; et al. (American Physical Society, 2016)
The branching fraction of the decay Bs0 → Ds(∗)+ Ds(∗)- is measured using pp collision data corresponding to an integrated luminosity of 1.0 fb^-1, collected using the LHCb detector at a center-of-mass energy of 7 TeV. It is found to be B(Bs0 → Ds(∗)+ Ds(∗)-) = (3.05 ± 0.10 ± 0.20 ± 0.34)%, where the uncertainties are statistical, systematic, and due to the normalization channel, respectively. The branching fractions of the individual decays corresponding to the presence of one or two Ds∗± are also measured. The individual branching fractions are found to be B(Bs0 → Ds∗± Ds∓) = (1.35 ± 0.06 ± 0.09 ± 0.15)%, B(Bs0 → Ds∗+ Ds∗-) = (1.27 ± 0.08 ± 0.10 ± 0.14)%. All three results are the most precise determinations to date.